Type II endometrial cancers: original research on a series - Nayak, B. L.; Misra, Sujata; Jaysingh, Suryakant; Giri, S. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Endometrial carcinoma, which ranks 3rd in India amongst the gynecological malignancies, is of two histological types: I and II. These differ in molecular as well as in clinical and histopathological profiles. Type II is estrogen independent, nonendometrioid, with higher grade histologies, more aggressive and carries an adverse prognosis. Methods: Endometrial carcinomas diagnosed from endometrial biopsies and hysterectomy specimens in the Dept of Gynaec-oncology, AHRCC, Cuttack from November 2009 to January 2015 were included in the study. All specimens were fixed in 10% neutral buffered formalin and paraffin embedded for histological examination with hematoxylin and eosin staining. The clinicopathological analysis of the cases of EC was done with an emphasis on morphology. Results: Of a total of 150 cases of EC reported, 20 cases were classified as type II EC (13.33%) as per histology. The age of the patients ranged from 36 to 73 years, with mean age is 61 years. In 11 cases (55%), the myometrial invasion was more than half. the histological type was a clear cell adenocarcinoma in 50% of the cases. All were treated with hysterectomy and chemotherapy. Conclusions: Of the type II EC, serous carcinoma is the most common type. Clinical presentation and prognosis differs in comparison to type I EC, thus the recognition of this type of EC is pivotal.